Romantic relationship obsessive-compulsive doubts, perfectionism, and DSM-5 personality traits in LGB people: a comparison with heterosexual individuals - Angelo, Nicole Loren; Brullo, Greta; Marsiglia, Alessandro; Tirelli, Alessandra; Piroddi, Elisa; Viti, Chiara; Aicardi, Ilaria; Pozza, Andrea (Frontiers in Psychology, 2024)
Relationship Obsessive-Compulsive Disorder is characterized by the presence of relationship-centered or partner-focused obsessions and compulsions that determine a great sense of doubt toward the partner or the relationship. Personality characteristics, including perfectionism, are involved in the development of Relationship Obsessive-Compulsive Disorder, and could predispose the individual to excessive doubts and preoccupations regarding the “adequacy of the couple” or the physical appearance of one’s partner. Evidence from epidemiological research shows that the LGB community can present a high risk and prevalence of obsessive-compulsive symptoms and recent research demonstrated the usefulness of the DSM-5 personality model in understanding the personality of sexual minorities. However, further research is necessary to deepen our knowledge of the relationship between these variables in the LGB community. The aim of the present study was to compare a group of heterosexual individuals to a group of LGB individuals regarding personality traits, perfectionism, and relationship obsessive-compulsive symptoms. A total of 200 participants, 98 in the heterosexual group and 102 in the LGB group, were enrolled in the study and completed a psychological battery comprised of the Obsessive-Compulsive Inventory-Revised, Personality Inventory for DSM-5, Relationship Obsessive-Compulsive Inventory, Partner-Related Obsessive-Compulsive Symptom Inventory, and Multidimensional Perfectionism Scale. The results show that LGB individuals tend to report greater feelings of doubt regarding the partner’s love, more negative emotions (Negative Affect) and Antagonism, and greater perfectionism traits compared to heterosexual individuals. These findings underline the necessity to consider the implementation of personalized interventions in clinical practice and the importance of initiating early preventive programs in sexual minority communities.